Advances in Pathogenesis and Therapeutics of Hepatobiliary Diseases (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue of Biomedicines, entitled “Advances in Pathogenesis and Therapeutics of Hepatobiliary Diseases,” presents cutting-edge research findings, innovations, and insights into a wide range of topics related to the hepatobiliary system, such as the molecular mechanisms underlying disease pathogenesis, diagnostic advancements, novel therapeutic approaches, and prevention strategies. The Special Issue comprises seven original articles and four review articles regarding NAFLD, primary biliary cholangitis (PBC), hepatitis B and C, and hepatocellular carcinoma (HCC).